ANALISIS HUKUM PENGATURAN PEMBINAAN NARAPIDANA LINGKUNGAN HIDUP DI LEMBAGA PEMASYARAKATAN - Yudha Ramadhan Subarja, Purna; Leonardo Lombok, Lesza; Junita Melo, Isye (At-Tanwir Law Review, 2025)
This study examines the rehabilitation of inmates in correctional institutions as an integral part of the criminal justice system in Indonesia, with a focus on the implementation of Law Number 22 of 2022 concerning Corrections. Using a normative legal research method, it was found that the inmate rehabilitation process occurs in stages, starting from observation, rehabilitation within correctional institutions, to social reintegration through assimilation programs and parole. Furthermore, special rehabilitation for inmates convicted of environmental crimes requires a different approach due to the complexity and extensive networks of the offenders. This special rehabilitation aims to increase ecological awareness, change offenders’ mindsets, and equip them with environmentally friendly skills, such as organic farming and waste management. The approach includes aspects of personality development, intellectual growth, self-reliance, as well as ecosystem rehabilitation programs and restorative justice, with strict supervision after release to prevent recidivism. The study’s findings emphasize that the success of inmate rehabilitation depends on the synergy among the government, correctional institutions, society, and families in creating effective and sustainable rehabilitation.